Singing and Deep Talk as Innovative Strategy to Motivate Students in Learning Arabic - Zainuddin, Zainuddin; Redi Zulpianto; Rosita Ilhami; Suci Ramadhanti Febriani; Tamim Adil (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2025)
Singing and deep talk are essential in learning because they stimulate emotions, strengthen social bonds, and deepen understanding and retention or the material. This study aims to discover strategies to motivate students to learn Arabic with singing and deep talk at the OCEAN Pare course institution. This study used a descriptive qualitative research method. The data were collected through classroom observation, semi-structured interviews with two purposively selected teachers and two students involved in the learning process, and analysis of relevant documents such as lesson plans and student assignments. Furthermore, the researcher analyzed the data through several steps, namely a) data reduction, b) data presentation, c) describe conclusions, and d) verification. The findings showed that singing and deep talk motivated students in learning Arabic. The increase in learning outcomes from an average of 30 to 80 indicated that there was improvement in learning. The benefits of integrating singing and deep talk: a) Increases learning motivation, b) Strengthens long-term memory, c) Develops listening and speaking skills, d) cultural understanding, e) Builds confidence in speaking Arabic, and f) Makes the learning process more fun and dynamic. The increase in learning outcomes from an average of 30 to 80 showed that  there was improvisation learning. This study contributed to understanding innovative strategies in language education by highlighting the unique combination of singing and deep talk as effective tools that enhanced student motivation, engagement, and proficiency in learning Arabic an approach that had been rarely explored in previous studies.